The Causes of The United States Launching A Trade War Against The People’s Republic of China (PRC) in 2018 - Lailah, Farihah Nishfah; Virgianita, Asra (Hasanuddin University, 2023)
The trade war between the United States and the People's Republic of China (PRC) has attracted world attention because it was predicted to affect the global economy. The trade war started with the United States implementing high import tariffs on PRC products, to which the PRC then responded with similar actions. The application of this tariff is a response to the trade deficit that occurred to the United States in its trade with China. The United States' trade deficit with China has existed since 1989. Meanwhile, in 2017, the United States and China agreed to implement a 100-day plan aimed at opening up and expanding trade between the two countries. Thus, the question in this research is